KRITIK SOSIAL DAN NILAI MORAL DALAM CERPEN “PERIHAL ORANG MISKIN YANG BAHAGIA” KARYA AGUS NOOR - Ihsan Aldi Putra (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Social criticism contained in literary works indicates irregularities in social life. Literature that is present in the midst of society can be used as a social controller. One of the literary works capable of this function is a short story. In every literary work including short stories, like other arts, made not only for entertainment. Furthermore, every work of art tries to convey a message about the values that the creator considers correct. In order to understand social criticism and values, the reader must first analyze it in order to grasp the meaning conveyed by the author. Therefore, through this article researchers are interested in discussing the things described above. This article analyzes the social criticism and moral values contained in the short story "Perihal      Orang Miskin yang Bahagia" by Agus Noor. The study uses the sociology of literature review as a research perspective. The resulting data is in the form of descriptions in the form of words because this research uses descriptive qualitative methods. The purpose of this research is to (1) describe the social criticism contained in the short story entitled "Perihal Orang Miskin yang Bahagia" by Agus Noor, (2) to describe the moral messages contained in the short story entitled "Perihal Orang Miskin yang Bahagia" by Agus Noor. Researchers found 13 findings of social criticism in the fields of politics, economics, culture, and law. While the moral values that were found were 5.